PENGENALAN POTENSI BUBBLE GENERATOR UNTUK MENDUKUNG AERASI BUDI DAYA IKAN DI MOYUDAN SLEMAN - Achilleus Hermawan Astyanto; Heryoga Winarbawa; Wibowo Kusbandono; Rines Rines; Doddy Purwadianto; Budi Setyahandana; Fransiscus Asisi Rusdi Sambada; I Gusti Ketut Puja; Fahra Diky Mustain; Stefano Jaladri; Muh Alif Atthayyah; Andra Justin Mathea (Universitas PGRI Yogyakarta, 2026)
Particularly, a bubble generator is a prospective and simple technology to be widely implemented during aeration purposes in aquaculture sectors. Here, amount of small air-bubbles which are produced can effectively maintain the dissolved oxygen concentration in the water with a longer time duration in comparison to several others conventional methods. Moreover, optimum geometry specifications may decrease its power consumption. Therefore, a soft introduction to the concept of this technology is necessary. Additionally, to ease on understanding of its theoretical concepts, a practical work is further of a great importance. It further deals with the acceleration of aquaculture’s production. Keyword: Aquaculture, Bubble Generator, Dissolved Oxygen.